Asset Optimization in Gili Air Island, Lombok - I Wayan Priyana Sudharma; Dian Ayu Rahmadani; Putu Ayu Meidha Suwandewi (Global Academia Publisher, 2021)
Gili Air Island is one of the three islands located in North Lombok Regency, Indonesia. It is a part of the Gili Tramena National Tourism Strategic Area. Tourism in Gili had been proliferating in 2013-2017. Due to the Lombok earthquake in mid-2018 and Covid-19 pandemic, however, tourism on the island has not yet reached its maximum potential. This paper applied Highest and Best Use (HBU) analysis to determine the most economic benefits an asset can provide. HBU analysis aims to determine whether or not the property is being used for its most profitable permitted use. The results of the HBU analysis show that the private villa covering an area of ​​1,144 m² results in an NPV value IDR20,100,000,000 and the land value is IDR3,090,000,000 or an increase of 85.47% from its original value.